Uji Selektivitas dan Penentuan Rekoveri Akhir pada Pemisahan Logam Emas dengan Metode Agregasi Hidrofobik - Suharta Suharta; N. M. Surdia; Buchari Buchari; Djulia Onggo (Jurnal Matematika & Sains, 2000)
STUDI APLIKASI METODE POTENSIOMETRI PADA PENENTUAN KANDUNGAN KARBON ORGANIK TOTAL TANAH The separation of substance by hydrophobic aggregation method is always started from colloidal particles. The flaws of this technique are especially in the selectivity and recovery. This research was developing of gold separation by hydrophobic aggregation method where it was started from solution system. Complex of [AuCl4]- was chosen in this solution system. The gold selectivity from cations {Ag(I), Cu (II), Fe (III), Zn (II), Pb(II)}, and anions {SO4 2-, NO3-, Br-, I-} was studied. As a result, this method can be separated of gold with height selectivity. The selectivity is restrained by pH, and the optimum pH is 2,0. The recovery of gold with DTMAB, TTMAB, and HTMAB surfactant is 92,60 ± 0,89 %; 90,30 ± 1,32 %; and 89,40 ± 1,51 % respectively.